Wprowadzanie elementów nauczania hybrydowego w kształceniu językowym; uzasadnienie dydaktyczne oraz główne wyzwania dla nauczyciela - Górecka, Joanna (Neofilolog, 2020)
The aim of the paper is to explore the potential of two Internet tools for asynchronous communication, wiki and forum, in oral tasks oriented at the development of argumentative skills. I assume that the use of these tools while preparing an oral task may positively influence the quality of the reflection further developed during class discussion, that is that the work performed in the virtual community context can reinforce the processes of the co-construction of knowledge in oral interaction. The paper focuses on several qualitative changes in the teaching process which can be initiated by hybrid construction of class scenarios. I discuss also selected difficulties connected with the introduction of this didactic innovation and the principal advantages of such scenarios at the level of the didactic relationship and teaching objectives.